From the Classical Tradition to the Symbolist Poetry: Tumanyan, Teryan, Charents - Burastan S. Zulumyan (Studia Litterarum)
Symbolism in Armenian poetry manifested itself at most in the works by Vahan Teryan and his follower Egishe Charents. Stemming from the classical heritage of Tumanyan, these two poets substantially reformed traditional verse on different levels, ideological, figurative, lexical, and metrical. The images of the Girl-Dream, Dreams, Other World, Twilight, Love-dispersed-in-th-world were new to the Armenian poetry at the beginning of the 20th century. Statistical the calculations of the groups of words with the meaning of the color (golden, silver, blue, sun, light, etc.), sound (voice, call, whisper, ringing, cry, silence, etc.), and words conventionally grouped as Upper World (self, soul, heart, sky, God, Universe, Dreams, Dream, etc.) demonstrate the difference in the poetics of Hovhannes Tumanyan, on the one hand, and Teryan and Charents on the other. The article juxtaposes semantic dominants of the poems and analyzes their stylistic properties with attention to their content and contexts. While Tumanyan’s poetic world is material and concrete and the language of his poems is traditional, symbolists develop a new poetical language that includes new lexical layers, neologisms and, most importantly, defamiliriazation of the ordinary words. The poet-demiurge creates a new symbolist meta-reality that results in a new poetic language and imagery.